The McDonaldization of Merdeka Belajar: How Globalized Standardization is Quietly Erasing Indigenous Indonesian Pedagogies - Iis Maisaroh; Selvy Ratna Sari; Elly Purwanti; Satwika Alhummaira (STIT Pringsewu, 2025)
This library research critically examines the Merdeka Belajar-Kampus Merdeka (MBKM) policy through the lens of George Ritzer’s sociological framework of McDonaldization to understand its impact on Indigenous Indonesian Pedagogies. As Indonesia aligns its higher education system with global neoliberal pressures for workforce readiness, the MBKM policy is championed as a movement for educational autonomy. However, utilizing Critical Discourse Analysis (CDA) and comparative juxtaposition, this study reveals a profound paradox: the policy’s implementation relies on rigid mechanisms of efficiency, calculability, predictability, and control that mirror the rationalization of the fast-food industry. The analysis demonstrates how accelerated degree pathways (Efficiency) and metric-obsessed performance indicators (Calculability) systematically erode traditional Javanese and Pesantren pedagogies, specifically values such as Ngeli (process-oriented depth) and Olah Rasa (emotional refinement). Furthermore, centralized digital platforms (Predictability) and app-based surveillance (Control) displace the context-specific wisdom of Kodrat Alam and the spiritual autonomy of the Pamong. The study concludes that MBKM facilitates the grobalization of Indonesian education, replacing locally significant cultural practices with globally standardized, empty forms (nothing). It advocates for a de-McDonaldization strategy that harmonizes administrative modernization with the preservation of Indonesia's holistic, character-driven educational heritage.